UNDERSTANDING THE BEAST OF SEXUAL HARASSMENT IN THE WORKPLACE (The Pretoria Student Law Review, 2021)
The field of labour law is an increasingly expansive one; however, one standard aspect remains common to it.1 This inescapable requirement usually involves the interaction of persons in a work environment, whether on an employee-to-employee basis or employer-to-employee level.2 In these interactions, events may arise that constitute a breaching of what is acceptable workplace conduct. A common instance of this is sexual harassment. Sexual harassment as defined in section 3(1) of the Code of Good Practice on the Handling of Sexual Harassment Cases (the Code) refers to ‘unwanted conduct of a sexual nature’.3 It may be physical, verbal or non-verbal acts. At times sexual harassment may receive a nonchalant response that insinuates the offended party somehow invited the sexual advances.4 In most cases, reasonable women do not complain about sexual harassment.5 This paper will seek to advance the perspective that this is not so and will do so by a critical analysis of various source materials. This is to the effect that the invalidity of this perspective will be critically exposed.
Keywords: labour law; sexual harassment; sexual harassment complaints